PERILAKU DISFUNGSIONAL AUDITOR TERHADAP KUALITAS AUDIT - Istanti, Sri Layla Wahyu (potensio, 2009)
In order to achieve accountability and transparency, the auditfunction is very essential. The audit results will providefeedback to all parties related to the company or organization.Audit opinion is not received a positive response becauseof the possibility of behavioral deviation by an auditorin the audit process. Dysfunctional behavior includes auditorsUnderreporting of time, premature sign-off (PMSO) andAltering/replacing of the audit procedure. This behavior iscaused by the locus of control (locus of control), personalperformance level of employees, the desire to stop working,self-esteem in terms of ambition, and commitment to theorganization. To overcome the impact of this behavior shouldKAP strict supervision of all auditors, and improve communicationwithin the audit team.Keyword: Dysfunctional behavior auditors, Audit quality